Implementation of Curriculum Kuttab Al-Fatih on Children at an Early Age - Wildan Saugi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
This research aimed to describe the implementation of the curriculum "Faith before Qur'an and Manners before Knowledge" on Children at an early age and to find out whether learning through play is implemented in Kuttab Al-Fatih. This research is field research with a qualitative approach. The data was collected through observation, interviews, and documentations, then analyzed and presented through descriptive techniques. The result shows that Kuttab integrates the internal curriculum with thematic learning of K13 of Early Childhood Education. The curriculum of Kuttab is supported by parents' participation. In the implementation of curriculum, faith and manners are firstly built when children enroll in kuttab and continuously strengthened during the learning process. Faith is built through stories and based on the method of delivering verses in the Qur'an. "Manners before Knowledge" is implemented through manners of education management, educating teachers as role models of manners, and preparation of student's manners before learning. The concept of "learning through play" is not implemented in Kuttab because learning has its manners.